Biology and behavior of Palpita flegia (Lepidoptera: Crambidae), White butterfly of tevetias (Apocynaceae) - Diodato, Liliana; Fuster, Andrea (Revista de Biología Tropical, 2018)
Palpita flegia (Cramer 1777) (Lepidoptera, Crambidae, is a pest insect that feeds on the foliage of Cascabela thevetia (L.) Lippold. The integrated management of the species a full knowledge about its biology and behavior. The objective of this study was to determine the number of larval stages and duration of biological phases in P. flegia under laboratory conditions, to determine the caloric requirements expressed in degrees days and to describe the ethological aspects of the species. Palpita flegia has six larval development stages. The larval phase lasted 25 days, the pupal phase 16 days, and adult survival was five days. This species requires 403.52 degree days for the development of the biological cycle. Population increases during fall with average temperatures of 15 °C and relative humidity of 60 to 75 %. Presence of the pupal parasitoid Brachymeria flegiae Burks, 1960 (Hymenoptera, Chalcididae) was verified. Sanitary pruning and conservation of natural enemies are indicated as measures for pest control.